Utility of Ultra-Widefield Retinal Imaging in the Follow-up and Management of Patients with Cytomegalovirus Retinitis. (18th May 2020) - Liscombe-Sepúlveda, John P.; Alba-Linero, Carmen; Llorenç-Belles, Víctor; Adán-Civera, Alfredo
ABSTRACT: Cytomegalovirus (CMV) retinitis is an opportunistic infection classically described in patients with acquired immune deficiency syndrome and other immune-compromising situations. As the diagnosis is based on clinical findings, classic retinal imaging montages have been a useful tool, being able to detect up to 140º of the retina. Since ultra-widefield (UWF) imaging systems have been available we can now detect more area of peripheral lesions in the diagnosis and follow-up of patients' response to antiviral treatment. We present a series of cases in which UWF was used as the main tool for diagnosis, monitoring, and management in patients with CMV retinitis.In all the cases presented, UWF imaging with fundus autofluorescence was able to capture peripheral CMV retinitis areas and discern active from inactive lesions. This, added to the comfort of use, seem to make UWF imaging a useful tool to detect changes in the follow-up of patients with CMV retinitis.